Quality of life measurement in acne. Position Paper of the European Academy of Dermatology and Venereology Task Forces on Quality of Life and Patient Oriented Outcomes and Acne, Rosacea and Hidradenitis Suppurativa. (10th October 2017) - Chernyshov, P.V.; Zouboulis, C.C.; Tomas‐Aragones, L.; Jemec, G.B.; Manolache, L.; Tzellos, T.; Sampogna, F.; Evers, A.W.M.; Dessinioti, C.; Marron, S.E.; Bettoli, V.; van Cranenburgh, O.D.; et al.
Abstract: Acne causes profound negative psychological and social effects on the quality of life (QoL) of patients. The European Dermatology Forum S3‐Guideline for the Treatment of Acne recommended adopting a QoL measure as an integral part of acne management. Because of constantly growing interest in health‐related QoL assessment in acne and because of the high impact of acne on patients' lives, the European Academy of Dermatology and Venereology Task Force on QoL and Patient Oriented Outcomes and the Task Force on Acne, Rosacea and Hidradenitis Suppurativa have documented the QoL instruments that have been used in acne patients, with information on validation, purposes of their usage, description of common limitations and mistakes in their usage and overall recommendations.